2020
DOI: 10.1136/bmjopen-2019-034135
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and clinical outcomes of patients with acute coronary syndrome: a meta-analysis

Abstract: ObjectivesAnxiety has been suggested to be associated with poor outcomes in patients with acute coronary syndrome (ACS). However, results of previous follow-up studies were inconsistent. The aim of this meta-analysis was to evaluate the association between anxiety and clinical outcomes in patients with ACS, and to investigate the potential role of depression underlying the above association.DesignA meta-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 41 publications
1
22
0
1
Order By: Relevance
“…14,16,23 Some studies found that the association between anxiety and long-term prognosis was insignificant after adjusted for depression. 23,34 And other studies shown the different results. 14,16 So in order to explore the potential influence of depression between anxiety and prognosis in patients with MI.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…14,16,23 Some studies found that the association between anxiety and long-term prognosis was insignificant after adjusted for depression. 23,34 And other studies shown the different results. 14,16 So in order to explore the potential influence of depression between anxiety and prognosis in patients with MI.…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies have confirmed that both depression and anxiety were associated with poor prognosis in patients with MI 14,16,23 . Some studies found that the association between anxiety and long‐term prognosis was insignificant after adjusted for depression 23,34 . And other studies shown the different results 14,16 .…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations